Atomistic modeling of La3+ doping segregation effect on nanocrystalline yttria-stabilized zirconia. Issue 19 (3rd May 2018) - Zhang, Shenli; Sha, Haoyan; Castro, Ricardo H. R.; Faller, Roland
Abstract : The effect of La 3+ doping on the structure and ionic conductivity change in nanocrystalline yttria-stabilized zirconia (YSZ) was studied using a combination of Monte Carlo and molecular dynamics simulations. Abstract : The effect of La 3+ doping on the structure and ionic conductivity change in nanocrystalline yttria-stabilized zirconia (YSZ) was studied using a combination of Monte Carlo and molecular dynamics simulations. The simulation revealed the segregation of La 3+ at eight tilt grain boundary (GB) structures and predicted an average grain boundary (GB) energy decrease of 0.25 J m −2, which is close to the experimental values reported in the literature. Cation stabilization was found to be the main reason for the GB energy decrease, and energy fluctuations near the grain boundary are smoothed out with La 3+ segregation. Both dynamic and energetic analysis on the Σ13(510)/[001] GB structure revealed La 3+ doping hinders O 2− diffusion in the GB region, where the diffusion coefficient monotonically decreases with increasing La 3+ doping concentration. The effect was attributed to the increase in the site-dependent migration barriers for O 2− hopping caused by segregated La 3+, which also leads to anisotropic diffusion at the GB.